2009
DOI: 10.1590/s0104-11692009000500013
|View full text |Cite
|
Sign up to set email alerts
|

Nasopharyngeal colonization with methicillin-resistant staphylococcus aureus and mortality among patients in an intensive care unit

Abstract: Fortaleza CR, Melo EC, Fortaleza CMCB. Nasopharyngeal colonization with methicillin-resistant staphylococcus aureus and mortality among patients in an intensive care unit. Rev Latino-am Enfermagem 2009 setembrooutubro; 17(5):677-82. (OR=1.02; p=0.97) o por causas infecciosas (OR=0.96; p=0.96 (OR=1,02; IC95%=0, p=0,97) ou por infecção (OR=0,96; IC95%=0,89; p=0,96 Nasopharyngeal colonization with Methicillin-resistant Staphylococcus aureus (MRSA) is common in critically ill

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 20 publications
0
5
0
Order By: Relevance
“…MRSA is an important agent of hospital-acquired protocols to prevent HAIs, isolation precautions and hand hygiene is recommended in order to control it (25) . Numerous studies illustrate that many different inanimate surfaces in hospitals can become a reservoir for MRSA .…”
Section: Discussionmentioning
confidence: 99%
“…MRSA is an important agent of hospital-acquired protocols to prevent HAIs, isolation precautions and hand hygiene is recommended in order to control it (25) . Numerous studies illustrate that many different inanimate surfaces in hospitals can become a reservoir for MRSA .…”
Section: Discussionmentioning
confidence: 99%
“…The APACHE II index values calculated at admission of the patient to the ICU, have been used to determine their severity and thus, together with other factors, identify the severity and the predictors of mortality in order to direct the assistance of health professionals (8) .…”
Section: The Apache II Index (Acute Physiology Andmentioning
confidence: 99%
“…Many studies have reported the presence of MRSA strains in the nasal mucosa, even at low levels, (2,(4)(5)(6)10,20) associated with greater morbidity and mortality. In the present study, the prevalence of MRSA was almost 10%, a value similar to that obtained in other studies involving hospitalized patients or health professionals.…”
Section: Discussionmentioning
confidence: 99%
“…(2) Staphylococcus sp., mainly S. aureus, is commonly found in the skin and mucosa of humans (especially in the anterior region of the nasal passages), being among the microorganisms most resistant to antibiotics. (3) It is one of the main pathogens that colonizes healthy individuals in the community, leading to infection in patients admitted in hospitals.…”
Section: Introductionmentioning
confidence: 99%